PROMOTING HOLISTIC FITNESS FOR ENHANCED HEALTH AND EFFECTIVE ENTREPRENEURSHIP IN THE 21 ST CENTURY NIGERIA - AGWUBIKE, E.O (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Fitness is the quality of life that pertains to physical, mental- emotional, and family social wellbeing. In order to promote holistic fitness for enhanced health and effective entrepreneurship, concerned individuals should embrace activities and programmes related to fitness promotion and disease prevention. They should be self-directed to be able to comprehend fitness promotion and disease prevention concepts and strategies. These will involve comprehending how their bodies function, ways to prevent diseases and other health/fitness problems, how their behavior influences their fitness status, and ways to promote fitness.